Study of the floristic composition of the seed bank in a caatinga area in the process of recovery (Research, Society and Development, 2021)
The Caatinga biome is predominantly formed by shruby-tree species, used by humans to feed animals, in addition to providing seeds for the natural regeneration process. This study identified the floristic composition in the seed bank of a caatinga area in recovery process located at Nupeárido Farm, Patos-PB, Brazil. In September 2016, fifty soil & litter samples were collected and taken to the CSTR/UFCG Forest Nursery facilities. These samples were irrigated daily for one year to quantify and identify the floristic composition of the seed bank. Species diversity and abundance were estimated using the Shannon-Wiener (H’) diversity and Pielou (e’) equitability indices. especially from the Poaceae and Convolvulaceae families. The West orientation showed greater species diversity (H’= 2.69) and more uniform distribution (e’= 0.47).